Penerapan Algoritma Floyd Warshall dengan Menggunakan Euclidean Distance dalam Menentukan Rute Terbaik - Darmadi Darmadi; T. M. Diansyah; Divi Handoko (LKP Unity Academy, 2023)
Path search is closely related to distance with searching at a location or place in a mapping in a search many heuristic algorithms are used. One of the algorithms used to determine the closest path is the floyd warshal algorithm which applies a heuristic function so that it will provide the most effective path search results. The problem that arises when the general public wants to find the nearest hospital is that there is no information that can be used as a medium that can determine the nearest hospital, therefore this study will apply the floyd warsahll algorithm with a distance formula that can be used to determine the best path or the closest distance To reach the nearest hospital, one of the distance formulas is the Euclidean Distance formula which is a calculation of the distance from 2 points in the Euclidean Distance space. the overall result of the calculation between the starting point or starting point with the end point or end node in the current case the starting point is at Permata Bunda Hospital which is assumed to be the starting point and ending point, namely the Madani Hospital. The results show that for a civil hospital the closest distance is 0.88 km which passes through nodes 2,3, and 4.